Muck drawing by inclined two-dimensional flow - Kalinichenko Olena; Fedko Mykhailo; Kushnerov Ivan; Hryshchenko Mykhailo (E3S Web of Conferences, 2019)
The work aims at studying and developing an efficient option of layer-by-layer muck drawing from the “dead area” of the footwall for the account of forming an inclined limiting contact of the muck ore with the unmined ore massif. The paper presents a detailed technical and economic analysis of factors and conditions impacting efficiency of muck drawing from the footwall “dead area”. The conducted studies of muck drawing on laboratory models considering a modeling scale enable determining optimal parameters of the layer-by-layer ore breaking and, further on, conduct a layer-by-layer muck drawing from the footwall “dead area” with minimum losses and dilution. The article determines regulations of the broken ore layer width considering possible obtaining of maximum muck values. On the basis of the conducted studies there are suggested optimal options of the technology of layer-by-layer breaking and drawing of the muck when forming an inclined limiting contact of the muck ore with the breakage face. The article proves practicability of breaking by inclined layers with formation of a limiting contact of the muck ore with the breakage face and suggests implementation of layer-by-layer muck drawing by an inclined flow.